1989
DOI: 10.1530/acta.0.1210203
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid antibodies during amiodarone treatment

Abstract: Abstract. In 44 euthyroid and goitre-free patients, 23 treated with amiodarone (group A) and 21 treated with other antiarrhythmic drugs (group B), antimicrosomal antibodies and antithyroglobulin antibodies were determined before the beginning of treatment and after 7, 15, 30, 60, and 180 days. In group A, none of the patients had antithyroid antibodies before treatment, 1 of 15 patients (6.7%) had antimicrosomal antibodies (titre 1:100) on day 7 only, and 1 of 18 (5.5%) had antithyroglobulin antibodies (titre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The prevalence of positivity for anti-TPO antibodies was similar to that in studies assessing the development of antithyroid antibodies in patients using amiodarone 42,43 . The high prevalence of thyroid dysfunction in anti-TPO-positive patients found in our case series (80%) suggests that patients with autoimmune thyroid disease are at a greater risk of developing hypothyroidism 44 .…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of positivity for anti-TPO antibodies was similar to that in studies assessing the development of antithyroid antibodies in patients using amiodarone 42,43 . The high prevalence of thyroid dysfunction in anti-TPO-positive patients found in our case series (80%) suggests that patients with autoimmune thyroid disease are at a greater risk of developing hypothyroidism 44 .…”
Section: Discussionsupporting
confidence: 74%
“…These results were not, however, confirmed in several subsequent prospective or cross-sectional studies (40 -44). Foresti et al (43) found positive thyroid autoantibody tests at low titer in only 2 of 23 amiodaronetreated patients, a figure not different from that found in patients receiving other antiarrhythmic drugs. Foresti et al (43) found positive thyroid autoantibody tests at low titer in only 2 of 23 amiodaronetreated patients, a figure not different from that found in patients receiving other antiarrhythmic drugs.…”
Section: Effect On Thyroid Autoimmunitymentioning
confidence: 84%